Evaluasi Mutu Layanan Pendidikan Kesetaraan pada PKBM Citra Ilmu di Semarang - Istiqomah, Nurul; Fakhruddin, Fakhruddin; Utsman, Utsman (Journal of Nonformal Education, 2017)
This study aims to describe the evaluation of the quality of equality education services in PKBM Citra Ilmu in Semarang Regency, as well as supporting factors and inhibiting factors. This research uses descriptive qualitative approach. Research subjects are founder, program leader, tutor, and learning residents. The data were collected by: (1) observation, (2) documentation, and (3) interview. Methods of data analysis conducted by: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions or verification. The results of this study reveal that: (1) service quality evaluation is able to face the challenge of education service for the future, (2) its supporting factor is accredited by institution and BAN-PNFI program, and the inhibiting factor is lack of proper salary for tutor.